Recent Progress in Targeted Drug Delivery Systems for Cancer Treatment - Ghadah Ali Al-Oudah; Thamer Mahmood, Noor; Fouad Mohammed, Dhelal (Journal of Biomedicine and Biochemistry, 2025)
Traditional cancer therapies are often limited by nonspecific distribution, leading to systemic toxicity and poor therapeutic outcomes. Targeted drug delivery systems aim to overcome these limitations by directing therapeutic agents specifically to tumor tissues, minimizing off-target effects. Recent advances have introduced sophisticated platforms, including nanoparticles, liposomes, dendrimers, micelles, and antibody-drug conjugates (ADCs). This review explores the design principles of these delivery systems, their mechanisms of targeting (passive via the enhanced permeability and retention effect and active via ligand-receptor interactions), and their clinical applications. Challenges such as drug resistance, immunogenicity, and tumor heterogeneity are also discussed. Future directions include stimuli-responsive systems, personalized nanomedicine, and combination therapies integrating immunotherapy and targeted delivery.